Enacting the interpretive turn: narrative means toward transformational practice in child protection social work - Turnell, Andrew (Curtin University, 2006)
This PhD project is undertaken by publication and thus this exegesis offers an explication and linking interpretation of the publications and DVD's listed in section two. The exegesis 'frames-up' what has been an ongoing interpretive inquiry exploring constructive frontline child protection social work undertaken by the author in collaboration with practitioners in Europe, North America and Australasia that has given rise to the publications and DVDs. Taking the lead from Geertz's ideas of interpretive anthropology the aim of this inquiry and publication work is to develop descriptions and theories of practice drawing upon insiders' local knowledges and sense-making of what constitutes good child protection social work. 'The natives' or insiders toward which this interpretive project directs its attention are first and foremost, frontline child protection social workers and wherever possible the child protection service recipients who have experienced the practice of those workers. The publication component of this project is a vital and integrated part of the research process since it is through the writing and production work that the usually overlooked, often deemed 'tacit' knowledges of service delivers and recipients are brought into the formal domain and made accessible to others.This project is undertaken with transformative intent. The first intent being to distil the wisdom of insiders' knowledges into richly detailed formal accounts of good practice that speaks directly to the practitioner's condition thereby enhancing their professional reflexivity, hope and capacity. The second intent is to provide constructive on-the-ground 'news of difference' for a child protection field that is over-organised by anxiety, worst-case outcomes and an obsession with managers' measures. The exegesis is formulated around the research question, What potential does interpretive social theory have for transforming child protection social work? My conclusion is that while interpretive social theory offers significant epistemological and methodological resources for transforming the practices and orientation of child protection social work, this potential will not be realised until the social work displays renewed ontological commitment and faith in the knowledges and everyday experience of frontline practitioners.